Lakótelep és társadalmi szegregáció - Csizmady, Adrienne (Szociológiai Szemle, 2024)
The main issue of the paper is how big is the danger of the accumulation of the different types of social conflict in the housing estates of Budapest. For this purpose the housing estates are studied as one of the sub-systems of the city systems of segregation. The data base of the analysis is offered by detailed census data in regional distribution studied with the help of statistical and spatial informatics. As a result the internal stratification of the sub-system of segregation of housing estates could be explored. Further on, hypotheses could also be worded about the interrelationships between such a stratification and the chances of the accumulation of poverty.